Simulation and Error Analysis of Non-orthogonal Face Gear Shaping - Zhao Ning; Jin Yongxian (Jixie chuandong)
Based on the principle of gear shaping， the process of non-orthogonal face gear shaping is simulated by using VERICUT. In addition， the influence of gear shaping error on tooth surface accuracy is explored by using the Matlab. First of all， the tooth surface equation of non-orthogonal face gear including machining error is deduceed based on the theory of gearing， and the coordinates of points of tooth surface is calculated by using the Matlab. Then， the machine tool model， cutter and gear billet are built in SolidWorks， and import them into VERICUT， the CNC program is written， the processing simulation is carried out， and comparing the processed model with the theoretical model， the correctness of NC shaping of face gear is verified. In the end， the coordinate system of measuring is established， a plan of measuring point range of working tooth surface is carried out， a method of calculating error of tooth surface is presented. A point-to-point quantitative and accurate comparation between the tooth surface with machining error and the theoretical tooth surface is carried out by numerical simulation of Matlab， and the influence of 3 common machining errors on tooth surface accuracy is summarized.